Practice of standard management of outpatient complaints (门诊投诉患者临床规范处理实践) - WANG Shengmei (王升梅); CHEN Jianyu (陈建玉); CHEN Mingxia (陈铭霞) (Association of Integrative Nursing, 2022)
Objective To observe the practice of standard management of outpatient complaints and improve the quality of outpatient medical care. Methods Total of 72 cases of outpatient complaints received from July 2020 to august 2020 were included as the control group, and another 72 cases of outpatient complaints received from September 2020 to October 2020 were included as the observation group. Cases of outpatient complaints in the control group were addressed by using a conventional method, and those in the observation group were addressed by using a standard management procedure. The incidence of medical dispute and patient satisfaction were compared between two groups. Results There were 6 cases of medical dispute reported in the control group. T he satisfaction rate was 98. 61%(71/72) in the observation group, which was higher than 84. 72%(61/72) in the control group. Conclusion Standardized treatment of outpatient complaints not only mediate doctor-patient disputes, but also protect the rights and interests of both sides. The practice of standardized treatment may improve the overall service quality of the hospital and the satisfaction of patients. (目的 探讨门诊投诉规范化处理的实践效果。方法 将2020年7月-8月接收的72份投诉案例设为对照组, 将2020年9月-10月接收的72份投诉案例设为观察组。对照组采取常规方法接待和处理, 观察组严格执行门诊投诉规范处置。统计2组医疗纠纷发生情况, 比较2组当事患者对处置过程的满意度。结果 观察组未发生医疗纠纷, 对照组发生医疗纠纷6(8. 33%)起。观察组当事患者对处置流程的满意度为98. 61%(71/72), 对照组为84. 72%(61/72)。结论 规范处置门诊投诉, 能够有效控制医患纠纷, 保障医患双方的权益, 有助于提高医院整体服务质量, 提升患者满意度。)